The Views And Energy Of Students Regarding The Implementation Of MBKM At The English Department Of Universitas Muhammadiyah Sidenreng Rappang - Andi Asrifan; Buhari Buhari; Ibrahim Manda (Prodi Pendidikan Bahasa Inggris, FKIP, LP3M Universitas Muhammadiyah Sidenreng Rappang, 2023)
A new rule known as Merdeka Belajar-Kampus Merdeka (MBKM), also known as Emancipated Learning - Independent Campus, aims to encourage students' independence in the development of their academic interests and motivation. Research on the implementation and effects of the MBKM Policy is still urgently needed because it is a new educational policy in Indonesia. This study aims to: 1) investigate English students' opinions of how the Merdeka Belajar-Kampus Merdeka Program has been implemented at the English Department of Universitas Muhammadiyah Sidenreng Rappang; and 2) investigate English students' intrinsic and extrinsic motivation to take part in the Merdeka Belajar-Kampus Merdeka Program. As many as 25 students from Universitas Muhammadiyah Sidenreng Rappang who participated in the MBKM program make up the sample of this study. Interviews and questionnaires were used to gather data. The findings showed that both intrinsic and extrinsic factors, including: 1) Intrinsic factors (challenging, curiosity, developing oneself, learning new things, increasing soft and hard skills, being an intelligent student and exploring the ability and knowledge); and 2) Extrinsic factors (getting a good job, getting the reward, gaining appreciation/praise from the environment, and getting money from the government), influence students to participate in the MBKM program. MBKM has been successfully implemented, in the opinion of the students of Universitas Muhammadiyah Sidenreng Rappang, and it has been well worth the effort. Students can benefit from learning support services such as the best experience, personal growth, better English proficiency, optimal learning, and significant advancement with the help of the MBKM Program. The MBKM Program's capacity to inspire students may have a favorable impact on their ability to advance professionally, improve their quality of life, and succeed academically.